Adapting a breast cancer early presentation intervention for Black women: A focus group study with women of Black African and Black Caribbean descent in the United Kingdom. (15th July 2022) - Marcu, Afrodita; Marke, Lorraine; Armes, Jo; Whitaker, Katriina L.; Ream, Emma
Abstract: Objective: Black women in the United Kingdom are more likely than White women to be diagnosed with advanced breast cancer and have lower survival rates. We consulted women of Black Caribbean and Black African descent in the United Kingdom on how the Promoting Early Presentation (PEP) booklet and intervention could be adapted for Black women to promote early presentation with breast cancer symptoms. Methods: Focus groups with 22 women of Black African and Black Caribbean descent, of whom five had been treated for breast cancer. The participants were recruited from a large UK breast cancer charity and community settings. Data were analysed using Framework Analysis. Results: Four themes summarised the participants' views on how the booklet and intervention could be adapted: Justify the focus on Black women, Black people do not talk about cancer, Make interventions inclusive and engaging, and Engage Black communities to deliver interventions . Conclusion: Breast cancer behaviour change interventions need to be more inclusive, illustrate how breast cancer symptoms manifest on black skin, and emphasise that breast cancer is curable to increase awareness and reduce cancer fear. Researchers should involve Black communities in the design and delivery of interventions to address appropriately cultural barriers to early presentation.